Profil Literasi Sains Peserta Didik pada Materi Hukum Newton Tentang Gravitasi di Tingkat SMA/MA - Afkar, Rian; Afrida, Juniar; Nasir, Muhammad (Intelektualita, 2024)
Scientific literacy is known as the ability to read, understand, evaluate, use scientific knowledge and information to think critically. This study aims to describe the scientific literacy ability profile of students on Newton's law of gravity at the level of MAN 1 Aceh Besar in physics lessons. In the context of scientific literacy includes competency and knowledge aspects. This research is in the form of a qualitative descriptive research carried out using a question instrument on aspects of competence and aspects of knowledge. The competence aspect contains three indicators, namely (1) explaining scientific phenomena with a percentage of 64%, (2) evaluating and designing scientific investigations with a percentage of 26%, (3) interpreting data and providing scientific evidence with a percentage of 43%. Then the knowledge aspect contains three indicators, namely (1) low-level cognitive gets a percentage of 54% with the predicate "less", (2) medium-level cognitive gets a percentage of 36% with the predicate "very less", (3) high-level cognitive gets a percentage of 20% with the predicate "very less".